2020
DOI: 10.1371/journal.pcbi.1008427
|View full text |Cite
|
Sign up to set email alerts
|

Speed of phototransduction in the microvillus regulates the accuracy and bandwidth of the rhabdomeric photoreceptor

Abstract: Phototransduction reactions in the rhabdomeric photoreceptor are profoundly stochastic due to the small number of participating molecules and small reaction space. The resulting quantum bumps (QBs) vary in their timing (latency), amplitudes and durations, and these variabilities within each cell are not correlated. Using modeling and electrophysiological recordings, we investigated how the QB properties depend on the cascade speed and how they influence signal transfer. Parametric analysis in the model support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It is indicated that each ommatidium contains different types of photoreceptor neurons, cone cells, pigment cells, secreted lenses and retinal cells [36][37][38]. Invertebrates' photoreceptor is rhabdomeric type [38][39][40], and the phototransduction process occurs within its. The phototransduction is mediated by a G-protein alpha-q (Gq)-coupled phospholipase C (PLC) signaling cascade among arthropods [16,41].…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that each ommatidium contains different types of photoreceptor neurons, cone cells, pigment cells, secreted lenses and retinal cells [36][37][38]. Invertebrates' photoreceptor is rhabdomeric type [38][39][40], and the phototransduction process occurs within its. The phototransduction is mediated by a G-protein alpha-q (Gq)-coupled phospholipase C (PLC) signaling cascade among arthropods [16,41].…”
Section: Discussionmentioning
confidence: 99%
“…In flies, phototransduction cascade adapts to light by decreasing the amplitude, latency and duration of QBs [ 31 ]. Shortening of QB latency is accompanied by a decrease in the spread of latencies, which, together with the narrowing of quantum bumps, underlies the shortening of multiphoton impulse response [ 41 , 42 ]. Since light adaptation is caused by LIC and associated with membrane depolarization, i.e.…”
Section: Discussionmentioning
confidence: 99%